Obtenção de carotenóides e flavonóides a partir do bagaço do pendúculo do caju por maceração enzimática - Barbosa, Manuella Macêdo (2010)
The artificial colorants such as solid yellow and orange GGN, have been worrying the world's population by its toxic nature. Instead of these compounds, alternative sources of natural dyes are being sought by researchers. The cashew apple pomace, a byproduct of the juice industry, has significant amount of carotenoids, compounds with coloring strength, biologically active, and containing flavonoids, is a promising source of natural dyes. This work aimed to study the acquisition of carotenoids and flavonoids from the cashew apple pomace by enzymatic maceration. To study the maceration was used cashew pomace from industry and a pectinolytic enzyme complex. In the first stage of this work, we selected the best parameters of proportion pomace: water, enzyme concentration, time and temperature of maceration, at bench scale, whose procedure was based on the determination of the parameter b of instrumental color. Once defined these parameters, the experiments were conducted at pilot plant scale, when extracts were obtained by five cycles of pressing / dilution steps. The extract was centrifuged, yielding a supernatant and a residue, which was concentrated under vacuum. Physicochemical characterization of crude extracts, concentrates and waste was performed. The results revealed that the best conditions for maceration of cashew apple pomace to obtain carotenoids were 30 ° C, 1:1 (pomace: water), adding 500 ppm of pectinolytic enzyme complex and incubation time of 1 hours. As for the content of flavonoids, the addition of pectinolytic enzyme preparation, combined with an increase of 10 ° C in temperature, increased the content of these compounds in the extracts. The concentration of the extract resulted decreased the levels of carotenoids, vitamin C and phenolic compounds gradually with increasing concentration levels.